Complex Analysis, Operators, and Related Topics 2000
DOI: 10.1007/978-3-0348-8378-8_5
|View full text |Cite
|
Sign up to set email alerts
|

On Embedding Theorems for Coinvariant Subspaces of the Shift Operator. I

Abstract: Weighted estimates are obtained for the derivatives in the model (shift-coinvariant) subspaces K p Θ , generated by meromorphic inner functions Θ of the Hardy class H p (C +). It is shown that the differentiation operator acts from K p Θ to a space L p (w), where the weight w depends on the function |Θ |, the rate of growth of the argument of Θ along the real line. As an application of the weighted Bernstein-type inequalities, new Carleson-type theorems on embeddings of the subspaces K p Θ in L p (µ) are prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 7 publications
1
72
0
Order By: Relevance
“…We finish by showing that (3) implies (1). By (ii), the operator T : l 2 −→ Y , (µ n ) −→ n µ n y n , already introduced above, is bounded and has dense range since by construction the canonical system is dense in l 2 and (y n ) n is dense in Y .…”
Section: Annales De L'institut Fouriermentioning
confidence: 75%
See 3 more Smart Citations
“…We finish by showing that (3) implies (1). By (ii), the operator T : l 2 −→ Y , (µ n ) −→ n µ n y n , already introduced above, is bounded and has dense range since by construction the canonical system is dense in l 2 and (y n ) n is dense in Y .…”
Section: Annales De L'institut Fouriermentioning
confidence: 75%
“…For one component inner functions we have already pointed out the following estimate by Aleksandrov (see [1])…”
Section: Annales De L'institut Fouriermentioning
confidence: 94%
See 2 more Smart Citations
“…It was shown that [for instance, [10], p. 355] arclength on {z ∈ D : |u(z)| = ε} is such a measure whenever is connected and η < ε < 1.A thorough study of the class I c was given by Aleksandrov [1] who showed the interesting result that u ∈ I c if and only if there is a constant C = C(u) such that for all a ∈ D Many operator-theoretic applications are given in [1][2][3]7]. In our paper here, we are interested in explicit examples, which are somewhat lacking in the literature.…”
mentioning
confidence: 99%